2024
DOI: 10.1029/2023jd039664
|View full text |Cite
|
Sign up to set email alerts
|

Storylines for Future Projections of Precipitation Over New Zealand in CMIP6 Models

Peter B. Gibson,
Neelesh Rampal,
Samuel M. Dean
et al.

Abstract: Large uncertainty exists in the sign of long‐term changes in regional scale mean precipitation across the current generation of global climate models. To explore the physical drivers of this uncertainty for New Zealand, here we adopt a storyline approach applying cluster analysis to spatial patterns of future projected seasonal mean precipitation change across CMIP6 models (n = 43). For the winter precipitation change signal, the models split roughly into two main groups: both groups have a very robust wet sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 114 publications
1
0
0
Order By: Relevance
“…Figure 1 shows ensemble mean changes in annual rainfall across the country, comparing projections of a modelled 3 • C world (hereafter '3 K experiment') relative to simulations of the current climate (hereafter 'Current Climate' experiment). Consistent with evidence from past studies (MFE 2018, Bird et al 2023, Gibson et al 2024, annual mean rainfall is found to increase by up to 10% along the western coastline of both islands (particularly the South Island), while comparable decreases in annual rainfall can also be detected over drier inland regions of the South Island, particularly 'rain shadow' regions on the leeward side of the Southern Alps, like South Canterbury and Central Otago. Both patterns of change are consistent with a strengthening of rain-bearing weather systems arriving from the west of the country, while…”
Section: Best-estimate Projections Of Annual Rainfall Changesupporting
confidence: 89%
“…Figure 1 shows ensemble mean changes in annual rainfall across the country, comparing projections of a modelled 3 • C world (hereafter '3 K experiment') relative to simulations of the current climate (hereafter 'Current Climate' experiment). Consistent with evidence from past studies (MFE 2018, Bird et al 2023, Gibson et al 2024, annual mean rainfall is found to increase by up to 10% along the western coastline of both islands (particularly the South Island), while comparable decreases in annual rainfall can also be detected over drier inland regions of the South Island, particularly 'rain shadow' regions on the leeward side of the Southern Alps, like South Canterbury and Central Otago. Both patterns of change are consistent with a strengthening of rain-bearing weather systems arriving from the west of the country, while…”
Section: Best-estimate Projections Of Annual Rainfall Changesupporting
confidence: 89%